Perencanaan dan Perancangan International Elderly Care Center di Ubud, Kabupaten Gianyar, Bali: Bahasa Indonesia - Krisna Adi Suryantara Putra; I Wayan Widanan; I Wayan Wirya Sastrawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Humans are basically social creatures who need each other. The human life span starts from the phase in the womb until death. The most difficult phase is lived when humans experience old age or can be called elderly (elderly) which starts from the age range of 60 years and over. Where the physical and psychological conditions of the elderly begin to decline. Thus the need to design a special elderly residence for foreigners located in Ubud, Bali. This residence will facilitate the elderly from abroad who want to live and settle in Bali. Here are some reasons why foreign elderly are the main target in designing this residence. The rise of foreign tourists who have retired from working in their respective countries choose to vacation and settle or enjoy old age in Bali, with an advanced age and not all hotels and resorts provide health services and not all hotel and villa resort facilities are elderly or disabled friendly, therefore an idea or idea was born in this planning. The data collection methods used in this paper are literature studies, field observations, and interviews with one of the administrators in charge of the Tresna Werdha Wana Seraya Social Home in Denpasar. Precedents or similar relevant projects related to the title. The results of the design of the International Elderly Care Center in Ubud, Gianyar, Bali are expected to be one of the centers for the care of foreign elderly in Ubud. With the potential of the Ubud tourism area that exists today and in the future.